Psychological Resilience of Healthcare Workers After the Covid-19 Pandemic: An Exploratory Study - De La Cruz, Isabella Paulina (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the psychological resilience of healthcare professionals in the National Capital Region (NCR) during the post-pandemic period. Specifically, it examined how individual, organizational, societal, and physiological factors influenced healthcare workers’ ability to adapt, recover, and sustain well-being following the COVID-19 pandemic. The study was anchored in Resilience Theory, the Transactional Model of Stress and Coping, and the Biopsychosocial Model. A qualitative phenomenological research design was employed to gain an in-depth understanding of participants’ lived experiences. Ten healthcare professionals, including physicians, nurses, and allied health workers, were purposively selected from various healthcare institutions in the NCR. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings revealed that resilience was influenced by a combination of personal strengths, adaptive coping strategies, workplace support, and external factors. Participants identified patience, empathy, emotional regulation, self-care practices, and a strong sense of purpose as essential qualities that enabled them to manage stress and maintain well-being. Structured routines, reflection, mindfulness, and support-seeking behaviors further strengthened resilience. Organizational factors such as supportive leadership, teamwork, effective communication, and access to mental health resources contributed positively to participants’ experiences. However, staffing shortages, excessive workloads, limited systemic support, delayed benefits, and inconsistent policy implementation posed significant challenges. Participants also emphasized the need for continuous mental health programs, supportive leadership, and adequate staffing to sustain resilience in the long term. The study concluded that post-pandemic psychological resilience among healthcare professionals is a dynamic and multifaceted process shaped by the interaction of personal, organizational, societal, and physiological influences. The findings highlight the importance of integrated interventions that strengthen both individual coping capacities and institutional support systems. The study supports Sustainable Development Goals 3 (Good Health and Well-Being) and 8 (Decent Work and Economic Growth) by promoting healthcare worker well-being and supportive work environments. Furthermore, it contributes to public health and institutional sustainability by providing insights that may guide workforce support initiatives, mental health programs, and organizational practices that foster long-term resilience in healthcare settings.
Keywords: Adaptation; Emotional Regulation; Healthcare Professionals; Mental Health; Post-Pandemic Resilience; Psychological Resilience; Support Systems; Well-Being